2021
DOI: 10.2478/bog-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

CSR&COVID19 – How do they work together? Perceptions of Corporate Social Responsibility transformation during a pandemic crisis. Towards smart development

Abstract: Nowadays, enterprises that are looking to achieve market success and maximise profits must not only offer good products or provide superior quality services, but also pay close attention to the environment in which they operate. One of the manifestations of concern for the broadly understood environment (society, environment) is Corporate Social Responsibility (CSR). For a good number of years, we have been observing changes in CSR trends, but the situation today demands that organisations update the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Corporate Social Responsibility disclosure merupakan laporan yang berisi informasi kuantitatif atau kualitatif dari dampak operasional perusahaan terhadap sosial dan lingkungannya yang akan menimbulkan konsekuensi bagi struktur finansial perusahaan (Bowrey & Clements, 2019). CSR disclosure menjadi alat komunikasi perusahaan dengan beberapa stakeholders, seperti konsumen, masyarakat, karyawan, dan lingkungan untuk merubah harapan dan persepsi mereka terhadap kinerja perusahaan (Lopata & Rogatka, 2021). CSR disclosure berperan menjadi alat evaluasi perusahaan dan menjadi bukti praktik akuntabilitas perusahaan (Irawan, Sumartias, Priyatna & Rahmat, 2022)…”
Section: Csr Disclosureunclassified
“…Corporate Social Responsibility disclosure merupakan laporan yang berisi informasi kuantitatif atau kualitatif dari dampak operasional perusahaan terhadap sosial dan lingkungannya yang akan menimbulkan konsekuensi bagi struktur finansial perusahaan (Bowrey & Clements, 2019). CSR disclosure menjadi alat komunikasi perusahaan dengan beberapa stakeholders, seperti konsumen, masyarakat, karyawan, dan lingkungan untuk merubah harapan dan persepsi mereka terhadap kinerja perusahaan (Lopata & Rogatka, 2021). CSR disclosure berperan menjadi alat evaluasi perusahaan dan menjadi bukti praktik akuntabilitas perusahaan (Irawan, Sumartias, Priyatna & Rahmat, 2022)…”
Section: Csr Disclosureunclassified
“…The study of literature (Boccia and Sarnacchiaro, 2020;Deng et al, 2020;Mahmud et al, 2020;Bapuji et al, 2020;Lopata and Rogatka, 2021;Mahmud et al, 2021;Zhang, 2021;Panagiotopoulos, 2021;Ahmed et al, 2021; showed that Corporate Social Responsibility activities related to the COVID-19 pandemic have varied across businesses, but a few common, major examples have been identified:…”
Section: Csr Activities Of a Business Related To The Covid-19 Pandemi...mentioning
confidence: 99%
“…Based on the existing publications, which confirm the reduction of corporate social responsibility (Lopata and Rogatka 2021;Ziogas and Metaxas 2021) and investment attractiveness of entrepreneurship (Falato et al 2021;Machokoto et al 2021) in the conditions of economic crises, the following hypothesis H1 is offered and tested: support for sustainable development in the conditions of an economic crisis requires the combination of financial risk management (inflow of investments) and corporate social responsibility (responsible use of investments for implementing the SDGs).…”
Section: Introductionmentioning
confidence: 99%